Disparitas Pemidanaan Terhadap Pelaku Permufakatan Jahat Melakukan Tindak Pidana Narkotika dalam Prespektif Tujuan Hukum - Muhammad Rusli Arafat; Sigid Suseno; Widiati Wulandari (Kosmik Hukum, 2023)
Law enforcement against narcotics trafficking is certainly a significant element in efforts to eradicate narcotics crimes. So it is interesting to observe the extent to which the perpetrators who cooperated in committing criminal acts of buying and selling narcotics were arrested, prosecuted and tried. This study aims to answer the problem of accountability of each perpetrator who cooperates in committing a criminal act of buying and selling narcotics and regarding the occurrence of criminal disparities in the case of cooperating to commit narcotics crimes by analyzing the legal considerations of the panel of judges, as well as answering the problem of criminal disparities in cases of cooperating to commit narcotics crimes based on the perspective of legal objectives. This research uses normative legal research methods. The results showed that, in the case of criminal acts of buying and selling narcotics with the inclusion of responsibility of the perpetrators, it must be proven whether as a pleger  (the main perpetrator), or  a medepleger (a person who participates). Because if it is not proven in the trial, it will have an impact on the unaccountability of the perpetrator. So the situation does not reflect justice and legal certainty. the concrete form of criminal liability is the imposition of punishment by the Panel of Judges in the form of imprisonment and fines, defendants who commit the same crime or the level of seriousness that can be equalized, are still sentenced to varying or different crimes. So that disparity in conviction becomes a phenomenon of injustice if the judge does not clearly provide a strong reason for distinguishing the sentence for the defendant in the case of cooperating in the criminal act of buying and selling narcotics.Keywords: Disparity, Conviction, Narcotics, Inclusion